Implementing Small Group Discussion and Gallery Activities for Elementary School Students’ Speaking Skills - Septina Asmaul Fauziah; Shirly Rizki Kusumaningrum; Ade Eka Anggraini; Radeni Sukma Indra Dewi (PT. Pusmedia Group Indonesia, 2026)
This study aims to identify the teaching techniques used by teachers in developing students' speaking skills and to describe the implementation stages, including pre-implementation, execution, and reflection. The study involved 28 fourth-grade elementary school students in the context of Indonesian language learning. A descriptive qualitative method was employed, with data collected through observation, interviews, and document analysis to capture the dynamics of classroom interaction. The findings reveal that the Small Group Discussion technique, when integrated with Gallery Walk activities, effectively enhances students’ speaking skills by providing structured opportunities to discuss, express ideas, and respond to peers’ work. In addition, this combination creates a more participatory and interactive learning environment, allowing students to gradually build confidence in speaking. Therefore, the integration of Small Group Discussion and Gallery Walk can serve as a practical and effective teaching technique to support the development of speaking skills in elementary education.